On the security of RFID devices against implementation attacks. (19th March 2010) - Hutter, Michael; Plos, Thomas; Feldhofer, Martin
Radio-Frequency Identification (RFID) is a wireless technology that already plays an important role in security-related applications. As soon as cryptographic features are integrated into RFID-enabled devices, the issue of implementation security becomes highly important. Implementation attacks exploit potential weaknesses of such devices and allow the extraction of sensitive information like secret keys. In this paper, we evaluate the efficiency of implementation attacks by conducting side-channel attacks and fault analysis on both High Frequency (HF) and Ultra-High Frequency (UHF) RFID tags. The results of our investigations disclose the potential vulnerability of RFID-tag implementations against practical attacks. Furthermore, this paper shows possible countermeasures that are optimised for resource-restricted devices like passive RFID tags.